2021
DOI: 10.1101/2021.02.17.21251943
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epidemiological and Genomic analysis of a Sydney Hospital COVID-19 Outbreak

Abstract: Early COVID-19 experience in Australia involved clusters in northern Sydney, including hospital and aged-care facility (ACF) outbreaks. We explore transmission dynamics, drivers and outcomes of a metropolitan hospital COVID-19 outbreak that occurred in the context of established local community transmission. A retrospective cohort analysis is presented, with integration of viral genome sequencing, clinical and epidemiological data. We demonstrate using genomic epidemiology that the hospital outbreak (n=23) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…This COVID-19 outbreak has similarities to other hospital-associated outbreaks. [6][7][8][9][10]20 Factors that contributed to the outbreak included failure to identify SARS-CoV-2 in admitted patients during the initial stages of infection, a largely incomplete or unvaccinated population, and patient behavioral factors such as a lack of compliance with physical distancing and mask wearing, with some patients wandering on the hospital unit. Roommates of COVID-19 patients were shown to be at a significantly higher risk of acquiring SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This COVID-19 outbreak has similarities to other hospital-associated outbreaks. [6][7][8][9][10]20 Factors that contributed to the outbreak included failure to identify SARS-CoV-2 in admitted patients during the initial stages of infection, a largely incomplete or unvaccinated population, and patient behavioral factors such as a lack of compliance with physical distancing and mask wearing, with some patients wandering on the hospital unit. Roommates of COVID-19 patients were shown to be at a significantly higher risk of acquiring SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we have shown the benefits of the outbreak investigation of adding WGS analysis. Other reports have highlighted the utility of WGS in outbreak investigation, 3,5,9,12,13,16,18,20,21 including its ability to identify complex outbreaks characterized by introduction of infections by >1 source or refute the original transmission hypothesis. WGS supported this study's hypothesis of the introduction of SARS-CoV-2 onto the unit by 2 patients who presented to the hospital with respiratory symptoms, one of whom was later found to have had community contact with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation